The Effectiveness of Using Big Book Media on Early Reading Skills in 5-6 Years Old - Oktaviana, Winda; Warmansyah, Jhoni; Trimelia Utami, Winda (Al-Athfal: Jurnal Pendidikan Anak, 2021)
Purpose – This study aims to determine the effectiveness of using Big Book media on early reading skills in children aged 5-6 years old.Design/methods/approach – This study used a quantitative approach which was carried out in an experimental method with a pre-post-test design. The sampling technique uses a simple random technique with 30 children. Data collection technique is by means of tests. The analysis technique for testing the hypothesis uses the difference test (t-test).Findings – The results showed that children in the experimental group who used Big Book media had a higher average score when compared to children in the control group who used magazine media. Based on the t-test calculation, findings indicate that there was a significant difference between the two groups. Thus, it can be concluded that the Big Book media is effective on early reading skills in children aged 5-6 years old.Research implications/limitations – This study was limited to one location, Mutiara Al-Madani Kindergarten, Jambi Indonesia, and with a small sample size, so the generalizability of the findings was also limited. It is necessary for future researchers to conduct studies with a wider scope and a more diverse population.Practical implications – The use of Big Book media can be an alternative learning media that can attract children's interests and can actively involve children in gaining rich literacy experiences in improving early reading skills.Originality/value – This study contributes to understanding of teacher's reference material in using learning media for early reading skills in children aged 5-6 years old. Paper type Research paper